<h3>I’ll teach you solve 3x^-2 and 5x^2y(2x^4y^-3)</h3>
——————————————
(A)
3x^-2
Apply exponent rule:
3*1/x^2
Multiply fractions:
1*3/x^2
Multiply the numbers:
1*3= 3
3/x^2
Your Answer Is ![\frac{3}{x^{2} }](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7Bx%5E%7B2%7D%20%7D)
(B)
5x^2y(2x^4 y^-3)
Apply exponent rule:
5y*2x^2+4 y^-3
Add the numbers:
2+4= 6
5y*2x^6 y^-3
Apply exponent rule:
5*2x^6 y^1-3
Subtract the numbers:
1-3= -2
5*2x^6 y^-2
Apply exponent rule:
5*2* 1/y^2 x^6
Multiply fractions:
1*5*2x^6/y^2
Multiply the numbers:
1*5*2= 10
10x^6/y^2
Your Answer Is ![\frac{10x^{6} }{y^{2} }](https://tex.z-dn.net/?f=%5Cfrac%7B10x%5E%7B6%7D%20%7D%7By%5E%7B2%7D%20%7D)
Plz mark me as brainliest if this helped :)
By using the formula pie radius squared times the height
Answer:
1. No 2.Yes 3.No 4.Yes
Step-by-step explanation:
Answer: $23
Step-by-step explanation:
1) 25-8=17
2) 17-4= 13
3) 13+10= 23
Matthew has $23 now
Answer:
y=13
Step-by-step explanation:
5+13=18